ANALISIS SWOT SEBAGAI STRATEGI PENGEMBANGAN USAHA KOPERASI MAKMUR MANDIRI - Perkasa, Ripho Delzy; Sitorus , Nurhidayanti; Siregar, Anna Wahyuni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Makmur Mandiri Cooperative is an economic entity that plays a crucial role in empowering the community through financial services and business development. In the dynamic context of business environment changes, cooperatives need to adopt the right strategies to strengthen their position in the market and achieve sustainable growth. One of the approaches used is the SWOT analysis, which enables cooperatives to identify strengths, weaknesses, opportunities, and threats that affect their performance and business development strategies. This journal aims to conduct an in-depth analysis of internal and external factors influencing Makmur Mandiri Cooperative and to formulate effective business development strategies. Through secondary data collection, observations, and interviews with relevant parties, this journal presents a comprehensive SWOT analysis, identifying strengths such as good reputation and loyal membership, weaknesses such as limited financial resources, opportunities such as market growth and new technologies, and threats such as intense competition and regulatory changes. The results of this SWOT analysis are then used as a basis for formulating effective action plans in the business development of Makmur Mandiri Cooperative. Proposed strategies include product diversification, effective marketing, utilization of information technology, and strategic partnerships.